UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN LEGUNDI (Vitextrifolia L.) TERHADAP PERTUMBUHAN Staphylococcus epidermidis - Jon Kenedy Marpaung; Panal Sitorus; Pandapotan Nasution; Roma Devina Yanti (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Legundi leaves (Vitextrifolia L.) contain flavonoid compounds, alkaloids and saponins, tannins, steroids/triterpenoidsthatact as antiseptic substancesandaid in the wound healing process. Staphylococcusepidermidis (Gram positive) is a mild skin infection-causing bacteria that accompanies the formation of abscesses. As for the purpose of this study To know the absence of antibacterial activity from concentrations of 10%, 15%, 20%, 25% legundileaf extractagainst Staphylococcus epidermid is bacteria and know the effective concentration of legunleaf extract in in hibiting the growth of Staphylococcus epidermidis bacteria. This research methoduses experimental methods and legundileaf extract with concentrations of 10%, 15%, 20%, 25%. The resultsshowedthatconcentrationsof 10%, 15%, 20%, 25% of legundileaf ethanol extract had antibacterial activity against the growth of Staphylococcus epidermidisindicated with a blockable zone diameter of 8 mm, 8.84 mm, 9.84 mm, 10.54 mm, respectively. Base dont here search that has beendone can be concluded that legundileaf extractcan inhibit the growth of bacteria Staphylococcus epidermidis, because around the discpaperthere is a clear zone that indicates the absence of bacterial growth.